A study of clinical profile of patients with chronic pulmonary obstructive disease at a tertiary care centre in North Karnataka, India - Gudagunti, Ashok Kumar; Hasabi, Ishwar; S., Arathy (International Journal of Advances in Medicine, 2019)
Background: Chronic pulmonary obstructive disease (COPD) has been responsible for the decreased quality of life as well as increased morbidity and mortality. Globally it has been estimated that nearly three million die yearly due to COPD and more likely to occupy the third place of mortality by 2030. The objective of the present endeavour was to study clinical profile of patients with chronic pulmonary obstructive disease at a tertiary care centre. Methods: A hospital based cross sectional study was carried out among 200 cases of COPD. Their detailed history, thorough clinical examination and parameters like hemoglobin, serum creatinine, protein etc were investigated. The presence of co-morbidities was noted. Results: As the age increased the prevalence of the COPD increased and highest was found out to be in the age group of above 60 years of age. Males were more affected with COPD as compared with females. The male to female ratio was found out to be 2.4:1. The smokers were more compared to the non smokers. The prevalence of smoking among COPD was noted to be 66% compared to 34% as non smokers. Least proportion of patients of the COPD had fever i.e. in 22% of the cases. Cough was found in 83% of the cases. Breathlessness was found out to be in 98% of the cases. 15% of the cases of the COPD had diabetes only as the co-morbidity along with COPD and no other co-morbidity. Conclusions: Breathlessness was the most common symptom at presentation and diabetes and hypertension were the most common co-morbidities found.